Implementasi Storyytelling Dalam Karya Dibalik Dapur Kebab Factory.id Sebagai Sutradara - Fahrudin, Irfan Azis; Melano, Fiqie Lavani (eProceedings of Management, 2024)
Mass communication plays an important role in delivering information, entertainment, and education to the public.One of its derivative products is audiovisual content, such as company profile videos, which companies use tointroduce their products and enhance their image. Kebab Factory.ID, a kebab MSME in Bandung, has experienced adecline in sales since 2022 despite promoting through social media. This research aims to implement storytelling inthe company profile video "Behind Kebab Factory.ID" as a director. The method used includes creating a 7-minutedocumentary video featuring the company's history, kebab-making process, flavor innovations, and testimonials fromcustomers and business partners. This video is designed to increase consumer attraction and trust in KebabFactory.ID with a strong storytelling approach and attractive visuals. The results show that storytelling in a companyprofile video is effective in conveying a deep and emotional message. The production process, including preproduction, production, and post-production, produces a quality video that captivates the audience. Theimplementation of storytelling proved to be an effective strategy to strengthen brand identity and attract consumers'attention in the digital era. Keywords-mass communication, Kebab Factory.ID, stoytelling, director.